2015
DOI: 10.1175/jpo-d-15-0067.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Wave Setup over a Steeply Sloping Fringing Reef

Abstract: High-resolution observations from a 55-m-long wave flume were used to investigate the dynamics of wave setup over a steeply sloping reef profile with a bathymetry representative of many fringing coral reefs. The 16 runs incorporating a wide range of offshore wave conditions and still water levels were conducted using a 1:36 scaled fringing reef, with a 1:5 slope reef leading to a wide and shallow reef flat. Wave setdown and setup observations measured at 17 locations across the fringing reef were compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 52 publications
4
81
0
Order By: Relevance
“…Buckley et al () detailed experimental measurements of wave transformation and setup dynamics across a scaled physical model of a coral reef‐fringed coastline conducted in a 55 m long wave flume (Eastern Scheldt Flume) at Deltares, in the Netherlands (Figure ). Here these data are further analyzed to investigate the total water level variability across the reef profile and runup at the shoreline.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Buckley et al () detailed experimental measurements of wave transformation and setup dynamics across a scaled physical model of a coral reef‐fringed coastline conducted in a 55 m long wave flume (Eastern Scheldt Flume) at Deltares, in the Netherlands (Figure ). Here these data are further analyzed to investigate the total water level variability across the reef profile and runup at the shoreline.…”
Section: Methodsmentioning
confidence: 99%
“…Coral reefs are often viewed as natural buffers to coastal storms by causing dissipation of SS waves through depth‐limited breaking and bottom friction (Cheriton et al, ; Ferrario et al, ; Quataert et al, ; Storlazzi et al, ). However, there have been few observations to quantify runup on reef‐fringed coastlines, and although reef morphologies clearly reduce the height of SS waves reaching a shoreline, there is evidence to suggest low‐frequency wave motions (Becker et al, ; Beetham et al, ; Merrifield et al, ; Nakaza & Hino, ; Nwogu & Demirbilek, ; Péquignet et al, ; Roeber & Bricker, ) and wave setup (Becker et al, ; Buckley et al, ; Quataert et al, ) can be enhanced in steeper reef environments relative to milder slope open coastlines. The latter is due to the dependence of wave setup on the cross‐shore profile of radiation stress gradients (Longuet‐Higgins & Stewart, ).…”
Section: Introductionmentioning
confidence: 99%
“…To account for the extra kinetic energy present in the roller, S84 separated the incident wave energy flux into a wave and a roller contribution as follows: Ef=Ef,w+Ef,r with Ef,w=ρgc1T0Tη2dt Ef,r=12ρrATc2 where ρ is the water density, g is the gravity constant, T is the wave period, η is the time‐varying surface elevation, and ρ r and A the surface roller mean density and area (see also Deigaard & Fredsøe, ). In practice, the surface roller constitutes the rotational part of the broken wave and accounts for the extra kinetic energy found in breaking and broken waves, see Svendsen (), Battjes (), and also the description of the roller model in Buckley et al (). Indeed, the term Ef,r represents the kinetic energy of the surface roller and the term Ef,w represents twice the wave energy flux calculated from the potential energy of the wave.…”
Section: Modeling Energy Dissipation Rates In Broken Waves With a Rolmentioning
confidence: 99%
“…implications in wave transformation (Buckley et al, 2015) and wave runup (Osorio et al, 2017). Therefore, the conservation of the dune during such conditions is fundamental for the natural protection of the coastal area.…”
Section: Discussion: Storm Impact During Hurricane Events 10mentioning
confidence: 99%
“…10 respectively). This is particularly important, since previous studies have demonstrated the importance of accurately predicting wave setup in the prediction of coastal hazards, including erosion and inundation due to storms (Sheppard et al, 15 2005;Vetter et al, 2010;Storlazzi et al, 2011;Baldock et al, 2014;Buckley et al, 2015).…”
Section: Numerical Model Validation 15mentioning
confidence: 99%